Challenges and opportunities in strategic educational planning: a systematic literature review - Endo, Semail; Busari, Abdul Halim; Abang Ibrahim, Dayang Kartini (International Journal of Evaluation and Research in Education (IJERE), 2025)
Strategic educational planning is essential for adapting to the evolving landscape of education, driven by socio-economic, technological and exceptional global health crisis. This systematic literature review explores the complex challenges and opportunities in strategic educational planning, synthesizing insights from diverse studies to provide a comprehensive understanding. The problem statement addresses the necessity for effective strategic planning to ensure educational resilience, quality and inclusivity amidst changing external conditions. To achieve this, we conducted an extensive search of scholarly articles from reputable databases such as Scopus and Web of Science, focusing on studies published between 2020 and 2024. The flow of study based on preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework. The database found (n=33) final primary data was analyzed. The finding was divided into three themes which is: i) educational strategies and innovations; ii) organizational and strategic management in education; and iii) impact and adaptation to external challenges in education. The review indicate that strategic educational planning must prioritize flexibility, stakeholder engagement and continuous improvement to navigate future challenges effectively. This review underscores the fundamental role of strategic planning in transforming educational systems to be more adaptive, inclusive and forward-thinking, ultimately enhancing their capacity to meet the diverse needs of learners in an ever-changing global context.